Physico-chemical properties and in vitro digestibility of edible films made from plantain flour with added Aloe vera gel - Gutiérrez Carmona, Tomy José (2016)
The aim of this study was to relate the physicochemical properties of edible films derived from plantain flour-glycerol containing different concentrations of Aloe vera (Av) gel to both their in vitro digestibility and sensory attributes, in order to contribute to the very few studies found in the literature. Films were prepared by casting. Degree of substitution, thickness, water solubility, water activity, swelling behavior, thermogravimetric analysis, X-ray diffraction, resistant starch, in vitro digestibility, color parameters and sensory evaluation were the tests carried out in this study. A clear relationship between the results demonstrated the effect of the Av gel on the cross-linking of the starchy matrix (plantain flour). This resulted in films with a higher resistant starch content and lower in vitro digestibility. The presence of Av gel slowed down starch digestion in the films, a feature which makes it potentially useful as a dietetic.